2014
DOI: 10.1038/ni.2957
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a G protein–coupled receptor by its endogenous ligand triggers the innate immune response of Caenorhabditis elegans

Abstract: Immune defenses are triggered by microbe-associated molecular patterns or as a result of damage to host cells. The elicitors of immune responses in the nematode Caenorhabditis elegans are unclear. Using a genome-wide RNAi screen, we identify the G-protein coupled receptor (GPCR) DCAR-1 as being required for the response to fungal infection and wounding. DCAR-1 acts in the epidermis to regulate the expression of antimicrobial peptides via a conserved p38 mitogen-activated protein kinase pathway. Through targete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
155
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(160 citation statements)
references
References 48 publications
(91 reference statements)
5
155
0
Order By: Relevance
“…38), but we observed that genetic ablation of dcar-1 did not rescue motility defects or neurodegeneration phenotypes caused by mutant TDP-43. These data suggest that other receptor proteins may be responsible for modulating neuronal degeneration in conjunction with TIR-1.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…38), but we observed that genetic ablation of dcar-1 did not rescue motility defects or neurodegeneration phenotypes caused by mutant TDP-43. These data suggest that other receptor proteins may be responsible for modulating neuronal degeneration in conjunction with TIR-1.…”
Section: Discussionmentioning
confidence: 66%
“…TIR-1 is an adaptor protein believed to mediate signalling downstream from an otherwise unknown cell surface receptor proteins. Recently, the dihydrocaffeic acid receptor DCAR-1 was identified as a component of the TIR-1 signalling pathway in response to epidermal infection 38 . We wondered whether DCAR-1 also contributed to neurodegeneration from mutant ALS proteins, but found that dcar-1 null mutations failed to suppress mutant TDP-43-mediated paralysis and motor neuron degeneration (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These might thus play more general roles in immunity, as most clearly demonstrated thus far for the nlp and cnc genes and their particular contribution to anti-fungal defence (e.g. [21,44,45]). It is worth noting that none of the considered effector genes show a change in expression after infection with Orsay virus (except downregulation of nlp-28).…”
Section: Future Challenges: Functional Evidence For Worm Immune Effecmentioning
confidence: 99%
“…Recognition of bacterial and fungal pathogens is less clear. A G protein-coupled receptor was implicated in the indirect recognition of the fungal pathogen D. coniospora via the perception of a so-called damage-associated molecular pattern (DAMP) [21]. Indirect pathogen detection also seems to be achieved through a cellular surveillance system, which activates pathogen defence responses when central cellular processes are disrupted [17,22].…”
Section: Brief Overview Of the Caenorhabditis Elegans Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation